A performance comparison of proactive and reactive routing protocols of Mobile Ad-hoc Network (MANET) - Azad, Saiful; Rahman, Md. Arafatur; Anwar, Farhat (Medwell Journals, 2007)
Mobile Ad-hoc NETwork (MANET) is a collection of wireless mobile nodes dynamically forming a temporary network without the use of any existing network infrastructure or centralized administration. To support MANET, many routing protocols are already designed, such as DSDV, DSR, AODV, TORA, OLSR, WRP, ZRP and many more. This study analyzes these three routing protocols using Network Simulator version no 2 (ns-2). The performance of these protocols are compared in terms of their packet delivery fraction, average end-to-end delay, normalized routing load and routing overhead (packets) for 50 nodes and 100 nodes model with various numbers of sources. However performance comparison and comparative analysis of these protocols for above mention metrics has not yet been performed. This study does that comparison and pointed out the relative strengths and weakness of those proactive and reactive routing protocols.